KEPUASAN PELAYANAN PUBLIK DI KECAMATAN KEDUNGKANDANG KOTA MALANG - Aisyah Anggita Rosmitha (Jurnal Ekonomi Pembangunan, 2011)
The research purpose is to find out about people satisfaction level to public service at Kedungkandang sub-district Malang city.   Analysis technique used in this research is tabulation analysis and public satisfaction Index  or analysis of all research data result. For the ten indicators in tabulation equation analysis, there found nine indicator stated that public satisfaction is quite enough, while one indicator stated that public satisfaction of public service is very satisfied. While for public satisfaction Index  analysis, there found overall index value found index number 66.12, so that public satisfaction in Kedungkandang sub-district  viewed from all indicators in public service stated quite satisfied but close to satisfaction index less satisfied because of convection result of public satisfaction Index value.